2021
DOI: 10.1177/01430343211000399
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mental contrasting with implementation intentions against solution-focused and autonomous planning

Abstract: Research suggests that mental contrasting with implementation intentions (MCII) enhances commitment and goal attainment. However, most studies have used limited comparison conditions. The present study compared MCII against two other potentially effective approaches: autonomous planning (AP), and solution-focused planning (SFP). It was thought that condition would have an indirect effect on goal progress by affecting commitment. However, goal attainment expectancy was hypothesised to be a moderator such that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The impact of implementation intent (i.e., planning to pursue a goal) on goal commitment has long been studied and found to be significant. For example, Abdulla and Woods (2021), when students were assigned to initially set goals for their personal projects, found that initial planning to achieve the goals, whether or not the approach to planning was well structured, enhanced goal commitment. Dalton and Spiller (2012) further found that implementation intention could explain goal commitment when there was only one goal rather than multiple goals.…”
Section: The Relationship Between Intention Goal Commitment and Behav...mentioning
confidence: 99%
“…The impact of implementation intent (i.e., planning to pursue a goal) on goal commitment has long been studied and found to be significant. For example, Abdulla and Woods (2021), when students were assigned to initially set goals for their personal projects, found that initial planning to achieve the goals, whether or not the approach to planning was well structured, enhanced goal commitment. Dalton and Spiller (2012) further found that implementation intention could explain goal commitment when there was only one goal rather than multiple goals.…”
Section: The Relationship Between Intention Goal Commitment and Behav...mentioning
confidence: 99%
“…However, doing so is not always cognitively straightforward, given that goal motives can influence an individual's propensity to persist or disengage. Although a variety of trainable strategies exist to facilitate goal persistence (Abdulla & Woods, 2021), sometimes decisions need to be made about when to adjust a goal. MCII has been identified as a promising candidate due to its capacity to encourage different self‐regulation responses based on the expected attainability of the goal (Kappes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%